COVID-19: the critical balance between appropriate governmental restrictions and expected economic, psychological and social consequences in Italy. Are we going in the right direction? - L'Angiocola, Paolo Diego; Monti, Manuel (Acta Biomedica Atenei Parmensis, 2020)
Since the declaration of COVID-19 pandemic infection by the World Health Organization, many governmental restrictions have been differently applied in the involved countries in order to contain the spread of the infection; Italy applied severe restrictive, public measures actually confining the entire population to an almost complete lockdown for several weeks; the restrictive quarantine can be considered controversial when excessively prolonged over time, due to many possible economic, psychologic and social consequences with a remarkable impact on the population. In this article we analyze possible collateral damages related to the prolonged quarantine.